NAD-modifizierte RNA: Redox-biochemie trifft RNA-Prozessierung - Höfer, Katharina; Jäschke, Andres (Biospektrum, 2018)
RNA is an important regulator in biology. Its simple architecture is augmented by diverse chemical modifications. Recently we discovered the ubiquitous redox coenzyme nicotinamide adenine dinucleotide (NAD) to be attached to a specific set of regulatory RNAs in bacteria in a cap-like manner, and to modulate the cellular functions of these RNAs. This article highlights the biosynthesis, removal, and biological function of this novel RNA modification.